Features of technical and tactical actions of female athletes of various qualifications specializing in complex swimming at a distance of 200 meters - Пилипко, Ольга (Slobozhanskyi Herald of Science and Sport, 2018)
Olga Pilipko Purpose: determine the features of technical and tactical actions of female athletes of various qualifications specializing in complex swimming at a distance of 200 meters. Material & Methods: analysis of literary sources, video shooting, timing, methods of mathematical data processing. The contingent of the surveyed were female athletes who specialized in complex swimming at a distance of 200 meters and had the level of sports qualification of the CMS, I and II adult category. Results: author established that the technical and tactical actions of female athletes of various skills during the crossing of the 200 meters distance by complex swimming have their own peculiarities; the degree of influence of the speed, pace and "step" indicators of the cycle of strokes on the result of the swimming of a distance of 200 meters in female athletes with a qualification level of CMS, I and II adults. Conclusion: determination of the specifics of the technical and tactical actions of female athletes of various qualifications specializing in complex swimming at a distance of 200 meters can serve as a guide for the construction of the training process, which will allow it to be improved in order to achieve high results.